PATTERNS OF SWITCHING IN INDONESIAN - ENGLISH BILINGUAL POP SONGS - Hartanti, Lina Purwaning (Paramasastra: Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2016)
Recently many studies are conducted to explore the use of code switching in everyday conversation, which is spontaneous. However, there has been little concern on how code switching is used in written data or prepared discourse. Thus, the recent phenomenon of using code switching in the lyrics of Indonesian – English bilingual pop songs, which are well-prepared, is illustrated in this paper. This paper focuses on the examination of the patterns of code switching between Indonesian and English in pop music genre, and whether these patterns are similar to the ones in everyday informal conversation, which is spontaneous. The data analysed in this paper were gained from a corpus consisting of the lyrics of 25 popular songs. Different patterns of switching are identified. It is suggested that the language mixture in the lyrics of Indonesian – English bilingual pop songs shows four different patterns of switching; they are conversational-style code switching, lexically motivated code switching, organizational code switching, and switching in English-dominant lyrics. Moreover, most of those patterns have similarity to those in everyday spontaneous conversation.